2022
DOI: 10.3390/nano12091490
|View full text |Cite
|
Sign up to set email alerts
|

Phosphosilicate Fiber-Based Low Quantum Defect Raman Fiber Laser with Ultrahigh Spectral Purity

Abstract: The phosphosilicate fiber-based Raman fiber laser (RFL) has great potential in achieving low-quantum defect (QD) high-power laser output. However, the laser’s performance could be seriously degraded by the Raman-assisted four-wave mixing (FWM) effect and spontaneous Raman generation at 14.7 THz. To find possible ways to suppress the Raman-assisted FWM effect and spontaneous Raman generation, here, we propose a revised power-balanced model to simulate the nonlinear process in the low-QD RFL. The power evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…An increased understanding of how manufacturing method influences the properties of these materials benefits new fibers generated from new compositions. Moreover, it has been reported that the quantum defect induced high thermal load in HPFLs can be effectively eliminated in phosphorus-doped fiber [480][481][482][483][484][485][486][487][488] and over the hundred-watt level fiber laser with less than 1% quantum defect [486] has been demonstrated. From a more intrinsic view of light-matter interactions, the increment of both P 2 O 5 and B 2 O 3 continues to reduce heat generation and decreases the value of dn/dT [36,37], which suppresses the induction to parasitic effects such as SBS and TMI as well.…”
Section: Summary and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased understanding of how manufacturing method influences the properties of these materials benefits new fibers generated from new compositions. Moreover, it has been reported that the quantum defect induced high thermal load in HPFLs can be effectively eliminated in phosphorus-doped fiber [480][481][482][483][484][485][486][487][488] and over the hundred-watt level fiber laser with less than 1% quantum defect [486] has been demonstrated. From a more intrinsic view of light-matter interactions, the increment of both P 2 O 5 and B 2 O 3 continues to reduce heat generation and decreases the value of dn/dT [36,37], which suppresses the induction to parasitic effects such as SBS and TMI as well.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…In addition to developing fiber lasers with higher output power and multi-dimensional controllability, there is an urgent demand for real-time analysis of laser beam characteristics, i.e., the mode decomposition (MD) [483][484][485][486][487][488][489][490][491]. Beam characterization represented by MD technology and beam quality measurement is an important tool for further study of fiber lasers.…”
Section: Summary and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The QD limits the conversion efficiency, but more importantly, it is the main source of thermal load in FLs. 31 Karimi: Contribution of different factors in heat production in Yb 3+ -doped fiber laser: a review Optical Engineering 110902-2 November 2022 • Vol. 61 (11) The Yb 3þ -doped FL has fewer QDs and an energy depletion mechanism.…”
Section: Quantum Defectmentioning
confidence: 99%
“…30 Also, phosphosilicate fiberbased RFL has great potential in achieving ultralow QD high-power laser output. 31 Tandem pumping brings the pump and signal wavelengths closer together and reduces the QD. 30 Another option is using the RFLs.…”
Section: Quantum Defectmentioning
confidence: 99%